The natural language processing workshop : design and build NLP projects confidently with this easy-to-understand guide /: design and build NLP projects confidently with this easy-to-understand guide. (2020) - Chopra, Rohan; Godbole, Aniruddha M; Sadvilkar, Nipun; Shah, Muzaffar Bashir; Ghosh, Sohom; Gunning, Dwight
No abstract available